Pengaruh Dewan Direksi Wanita, Dewan Komisaris Wanita Dan Kualitas Pengungkapan Corporate Social Responsibility Terhadap Manajemen Laba - Bimahadi Razak; Herlina Helmy (Universitas Negeri Padang, 2020)
This study examines the effect of female boards of director, female boards of commisiioners, and the quality of corporate social responsibility disclosure on earnings management. This research is a type of causative research. This population in this study are companies listed on Indonesia Stock Exchange (IDX) and publish sustainability reports in 2015-2018. The research sample was obtained using purposive sampling methodwhich resulted 76 observations. The dependent variable earnings management is measured using the discretionary accrual proxy of the Modified Jones Model (1991). The independent variable of female boards of director and female boards of commisiioners is measured using dummy variables, while the quality of corporate social responsibility disclosure is measured using the content analysis method adopted from the research of Anggraini and Djakman (2017). The results of this study explain that women boards of director, women boards of commissioners and the quality of corporate social responsibility disclosure have no significant effect on earnings management practices. For further research, it is better to focud in one industrial sector only, add other independent variables and increase the research time span so that it will give better results.